2020
DOI: 10.26434/chemrxiv.11996970.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

124I-Radiolabeling of a Au(III)-NHC Complex for in Vivo Biodistribution Studies

Abstract: Au(III) complexes with N-Heterocyclic Carbenes (NHCs) ligands have shown remarkable potential as anticancer agents, yet their fate in vivo has not been thoroughly examined and understood. Herein we report on the synthesis of new Au(III)-NHC complexes via direct oxidation with radioactive [124I]I2 as a valuable strategy to monitor the in vivo biodistribution of this class of compounds using positron emission tomography (PET) and, in combination with in vitro analyses, to provide direct evidence of the i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Surprisingly, this fundamental aspect is often overlooked, particularly in work on Au(III)-NHCs (NHC, N-heterocyclic carbene) and their mode of action. [55][56][57][58] Despite the deliberate use of ligands known for their robust σ-donating and π-accepting properties, 59 i.e., nor-Fig. 3 Comparison of the activity profile of commercial drugs with a known mode of action, the previously patented Au(Me 2 Pyrr) and Au (PrPyrr), 52 and AuL1 synthesised in this work.…”
Section: Reaction Of Aul1 With Gshpostulated Mechanism Of Actionmentioning
confidence: 99%
“…Surprisingly, this fundamental aspect is often overlooked, particularly in work on Au(III)-NHCs (NHC, N-heterocyclic carbene) and their mode of action. [55][56][57][58] Despite the deliberate use of ligands known for their robust σ-donating and π-accepting properties, 59 i.e., nor-Fig. 3 Comparison of the activity profile of commercial drugs with a known mode of action, the previously patented Au(Me 2 Pyrr) and Au (PrPyrr), 52 and AuL1 synthesised in this work.…”
Section: Reaction Of Aul1 With Gshpostulated Mechanism Of Actionmentioning
confidence: 99%
“…In cancer and normal cells, the activity of the TrxR enzyme is essential for cell growth and survival; therefore, it might be viewed as a target for research on antitumor chemotherapy and other diseases. , In the literature, there are a large number of gold compounds that target the mitochondrial and cytoplasmic TrxR and can overcome resistance to traditional drugs such as cisplatin. ,, Soft metal ions such as Au 1+ and their coordination compounds show high affinity for −SH or −Se – residues, which leads them to specifically target proteins or enzymes containing thiol and selenates groups. , Thereby, gold­(I) complexes have been considered as potential chemical agents for cancer therapy. ,, Indeed, crystal structures of gold–protein adducts have evidenced that Au I –S covalent bonds with active-site thiols are responsible for the strong inhibition of the enzyme activity. , Gold­(III) complexes have also been profiled as important chemotherapeutic agents. ,, Indeed, results have shown that stable gold­(III) complexes act at the interface of the TrxR dimer, showing an effective inhibitory effect of TrxR action. , Gold­(III) complexes are less stable than platinum­(II) analogues under physiological conditions and can be easily reduced to Au I derivatives by intracellular thiols such as glutathione (GSH) and cysteine (Cys) or by disulfide-reductase enzymes. ,,, The oxidation of these biomolecules leads to the formation of the RSSR sulfur-bridged dimers (2RSH → RSSR + 2H + + 2e – ), providing the electrons for gold­(III) complex reduction. , Studies of reaction mechanisms for gold­(III) complexes in the cellular environment are scarce. ,, However, it is evident that the ability of gold to form stable complexes is an important factor to improve their behavior under physiological conditions and, at the same time, for their biological action mechanisms. The perspective of Glišić et al about the reactivity of gold­(III) complexes containing N-donor ligands and chlorine concluded that the reactions with sulfur-containing amino acids and peptides primarily proceed through reduction of Au III and oxidation of the sulfur side chain.…”
Section: Introductionmentioning
confidence: 99%